Research on the evaluation system of smart tourism projects based on user experience. (26th November 2021) - Wang, Yipeng
In recent years, with the rise of smart tourism, many tourist attractions invest a lot of money to build smart tourism projects to make tourism more intelligent. In order to evaluate the problems in the use of such projects and point out the direction of improvement, this paper proposes a smart tourism evaluation index system based on user experience. The evaluation index system probes into the actual feedback data of the users in the tour process from users' sensory experience, program experience, content experience and related experience. Then, the author utilise the fuzzy comprehensive evaluation method to process the collected data to obtain the evaluation index under the framework of the index system. In the application of this evaluation index system, it is compared with the commonly used evaluation index system in industry to point out the advantages and disadvantages of smart tourism projects and the direction of improvement more directly and effectively.